2024
DOI: 10.1039/d3cc04342h
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemically synthesized hydride-stabilized boron nanosheets via radical-assisted oxidative exfoliation for energy storage applications

Anandhakumar Sukeri,
Swati Panigrahi,
Kothandaraman Ramanujam

Abstract: Metal-free hydride stabilized boron nanosheets were synthesized in an aqueous medium in mg scale and their suitability as an anode material for Li-ion batteries in half-cell mode was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The hydrogenated borophene has been demonstrated to be a stable 2D Dirac material with an ultra-high Fermi velocity, which has 4 times higher Fermi velocity than graphene. 239−241 Sukeri et al 242 synthesized hydride BNSs (H-BNS) with high environmental stability, demonstrating excellent oxidation and reduction capabilities resulting in high specific capacity, excellent rate capability and capacity retention in Li-ion batteries. Li-doped borophene and Ca-Coated BNTs were reported to be good materials for hydrogen storage.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogenated borophene has been demonstrated to be a stable 2D Dirac material with an ultra-high Fermi velocity, which has 4 times higher Fermi velocity than graphene. 239−241 Sukeri et al 242 synthesized hydride BNSs (H-BNS) with high environmental stability, demonstrating excellent oxidation and reduction capabilities resulting in high specific capacity, excellent rate capability and capacity retention in Li-ion batteries. Li-doped borophene and Ca-Coated BNTs were reported to be good materials for hydrogen storage.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Zhou et al discovered that by functionalizing the surface of BNSs, they were able to obtain methyl-functionalized BNSs with excellent resistance to oxidation, allowing them to remain stable at 250 °C, and these functionalized BNSs exhibited specific cycling and rate performances in Li-ion batteries. The hydrogenated borophene has been demonstrated to be a stable 2D Dirac material with an ultra-high Fermi velocity, which has 4 times higher Fermi velocity than graphene. Sukeri et al synthesized hydride BNSs (H-BNS) with high environmental stability, demonstrating excellent oxidation and reduction capabilities resulting in high specific capacity, excellent rate capability and capacity retention in Li-ion batteries. Li-doped borophene and Ca-Coated BNTs were reported to be good materials for hydrogen storage. The addition of oxygen to the borophene chain was thought to improve its structural stability and electrical conductivity. , Joshi et al demonstrated remarkable stability of boron nanosheets with oxygen defects in aqueous solutions, as well as splendid pseudocapacitive charge storage and excellent cycling stability in aqueous supercapacitors.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%